Perancangan Alat Kunci Pintu Pintar Menggunakan Master Card Berbasis Arduino Nano - Ryo Andika Manrasul; Zahir Dwiyan Nugroho; Agung Yudantara; Sri Muryani (INSANtek, 2021)
The crime rate, wich is increasing day by day, raises concerns about the security of storing data files and important documents of an educational institution. The number of data thefts and data file storage devices is due to the ease of the perpetrators of theft accessing an office room of the relevant agency caused by the weakness of the locking security systems in certain rooms. Over time, innovations began to be made to create a tool design that functions optimally. And an example of the applications in this case is a key that is connected to security. This is the security of a private room with a smart door lock wich is currently very diverse and growing, the type and level of security as well. In this case, an idea was created to make a smart door lock security design with a fairly capable level of securiy, namely using an RC552 RFID sensor syestem that can read teh UID master card. The system is connected to an arduino nano microcontroller that proccesses a user’s access door program with a specific purpose. With access that is only owned by certain users so that the privacy and security of a data storage room can be guaranteed that can minimize the level of crime and data theft in a educational institution room.